Maternal genomic variability of the wild boar (Sus scrofa) reveals the uniqueness of East‐Caucasian and Central Italian populations - Saber Khederzadeh; Szilvia Kusza; Cui‐Ping Huang; Nickolay Markov; Massimo Scandura; Elmar Babaev; Nikica Šprem; Ivan V. Seryodkin; Ladislav Paule; Ali Esmailizadeh; Hai‐Bing Xie; Ya‐Ping Zhang (Ecology and Evolution, 2019)
Abstract The phylogeography of the European wild boar was mainly determined by postglacial recolonization patterns from Mediterranean refugia after the last ice age. Here we present the first analysis of SNP polymorphism within the complete mtDNA genome of West Russian (n = 8), European (n = 64), and North African (n = 5) wild boar. Our analyses provided evidence of unique lineages in the East‐Caucasian (Dagestan) region and in Central Italy. A phylogenetic analysis revealed that these lineages are basal to the other European mtDNA sequences. We also show close connection between the Western Siberian and Eastern European populations. Also, the North African samples were clustered with the Iberian population. Phylogenetic trees and migration modeling revealed a high proximity of Dagestan sequences to those of Central Italy and suggested possible gene flow between Western Asia and Southern Europe which was not directly related to Northern and Central European lineages. Our results support the presence of old maternal lineages in two Southern glacial refugia (i.e., Caucasus and the Italian peninsula), as a legacy of an ancient wave of colonization of Southern Europe from an Eastern origin.